Performing bodies : female illness in Italian literature and cinema (1860-1920) - Ramsey-Portolano, Catherine (Fairleigh Dickinson University Press series in Italian studies., 2018)
This book examines how in Italian literature and film, as well as in society, women were confined to traditional roles and illness often represented the consequence for transgressing those roles. Feigning illness offered women a way to "own" the illness and become masters of their bodies as well as their stories and destinies.